Cilostazol adjunctive therapy in treatment of negative symptoms in chronic schizophrenia: Randomized, double‐blind, placebo‐controlled study. (18th April 2017) - Rezaei, Farzin; Mesgarpour, Bita; Jeddian, Alireza; Zeionoddini, Atefeh; Mohammadinejad, Payam; Salardini, Elaheh; Shahriari, Mona; Zeinoddini, Arefeh; Akhondzadeh, Shahin
Abstract: Objective: To evaluate the efficacy and safety of cilostazol, a selective inhibitor of phosphodiesterase III, as an adjunctive to risperidone in alleviating the negative symptoms of schizophrenia. Methods: Eighty‐four in‐patients with diagnosis of chronic schizophrenia participated in a randomized, placebo‐controlled trial and underwent 8 weeks of treatment with either cilostazol (50 mg twice a day) or placebo as an adjuvant to risperidone. Participants were assessed using the positive and negative syndrome scale (PANSS) at baseline and at weeks 2, 4, 6, and 8. The primary outcome measure of the trial was to evaluate the efficacy of cilostazol compared to placebo in improving the PANSS negative subscale score. Result: General linear model repeated measures demonstrated significant effect for time × treatment interaction on negative subscale scores ( p < .001) and PANSS total ( p = .006) but did not demonstrate significant effect on the PANSS positive ( p = .37) and general ( p = .06) subscales. Frequency of adverse events was not significantly different between the 2 treatment groups. No serious adverse event was observed. Conclusion: An 8‐week course of treatment with cilostazol as an adjunct to risperidone showed a favorable safety and efficacy profile in patients with schizophrenia.